Programming Multi-Agents Systems 9th International Workshop, ProMAS 2011, Taipei, Taiwan, May 3, 2011. Revised Selected Papers - Dennis, Louise; Boissier, Olivier; Bordini, Rafael H. (Lecture Notes in Artificial Intelligence,, 2012)
This book constitutes the proceedings of the 9th International Workshop on Programming Multi-Agent Systems held in Taipei, Taiwan, in May 2011 in conjunction with AAMAS 2011, the 10th International Joint Conference on Autonomous Agents and Multiagent Systems. The 12 revised full papers presented together with 1 invited paper were carefully reviewed and selected for inclusion in the book. The papers are organized in topical sections on foundations of agent programming languages; multi-agent oriented programming; model checking; and papers of the participants of the multi-agent programming contest.